Outcomes of Primary Tibiotalocalcaneal Nailing for Complicated Diabetic Ankle Fractures. Issue 4 (16th October 2019) - Ebaugh, M Pierce; Umbel, Benjamin; Taylor, Benjamin; Goss, David
Category: Trauma, Ankle, Ankle Arthritis Introduction/Purpose: Ankle fractures in complicated diabetic patients (i.e. presence of neuropathy, nephropathy, or peripheral vascular disease) have significantly increased rates of complications with markedly worse functional outcomes. Current management advocates for operative intervention due to high rates of fracture reduction loss and Charcot arthropathy in those treated nonoperatively. Tibiotalocalcaneal (TTC) nails have been reported in the literature as a salvage option when initial ankle stabilization has failed. We hypothesize that the minimally invasive, robust construct that primary TTC fixation with an intramedullary nail offers will result in high rates of limb salvage, acceptable rates of complications, and nominal loss of function. Thus, the purpose of this study was to evaluate the outcomes of primary TTC intramedullary nailing for definitive treatment of neuropathic ankle fractures. Methods: This was an IRB approved retrospective study of 27 complicated diabetic patients who underwent TTC nailing of their ankle fracture as a primary treatment without formal joint preparation. The study was undertaken at an urban Level 1 trauma center. Complicated diabetes was defined as having one or more of the following formal diagnoses: neuropathy (20 patients), nephropathy (4), PVD (3). Mean clinical follow up was 888 days (range 21-2843 days). Patients were screened for associated risk factors such as open fracture, neuropathy, nicotine and alcohol abuse, obesity and elevated Hba1c. Data was also collected on surgical complications such as superficial and deep infection, wound dehiscence, amputation, revision fixation, hardware failure, malunion, nonunion. Outcomes were measured in length of hospital stay, loss of ambulatory level, and time to death. Results: The mean age was 66 (32-92) years with an average BMI of 38 (21-68). Six of 27 fractures were open and 20 of 27 patients were neuropathic. Mean hemoglobin A1C was 7.4 (5.5-13). Average hospital stay was 6 days (0-22). The average patient was fully weight bearing at 6 weeks (1-17). Two patients underwent removal of hardware, due to pain and proximal screw failure respectively. One patient required formal arthrodesis. There were no malunions, symptomatic nonunions, or instances of Charcot arthropathy. Two patients underwent repeat debridement for infection, resulting in antibiotic nail placement and above knee amputation respectively. A total of eight patients had died by final follow up (mean 1048 days) from index procedure. Overall, mean ambulatory status was maintained. Conclusion: Primary tibiotalocalcaneal nailing is a viable alternative to previously described methods of fixation of complicated diabetic ankle fractures. With high limb salvage rates, early weight bearing, maintained ambulatory status and low rates of return to the operating room, our technique can be considered an applicable approach to increase overall survivability of threatened limbs and lives with acceptably low complications.